DEVELOPMENT OF STUDENTS’ CRITICAL THINKING ABILITY ASSESSMENT INSTRUMENTS BASED ON MULTIPLE REPRESENTATIONS ON STOICHIOMETRY MATERIAL - Hamidatun Nisa; Ajat Sudrajat; Tita Juwitaningsih; Jasmidi Jasmidi (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the results of the analysis of instrument requirements and the analysis of multiple representation-based stoichiometric material concepts used to measure students’ critical thinking skills; the results of the feasibility test of the assessment instrument based on Aiken’s index of expert validity; test results on the level of problem difficulty, reliability, discriminatory power and distractibility using Rasch modeling; the level of students’ critical thinking skills as measured by the critical thinking ability assessment instrument; and student responses to the assessment instruments developed. The development model used in this study is a 4-D model consisting of define, design, develop, and disseminate stages. Based on the results of the needs analysis and the results of the material analysis, it was found that the assessment instrument for chemistry learning outcomes had not been able to measure students’ critical thinking skills, and the stoichiometric material studied was following the basic competencies in the revised 2013 curriculum; assessment instrument for critical thinking skills based on multiple representations consists of 25 items. The results of the expert validation test are based on Aiken’s index with high criteria of 0.81 and the results of the material validation index by teachers with medium criteria of 0.78. Empirical validation test with Principal Component Analysis (PCA) obtained 8 variance factors of 80.174% with the eigenvalues fulfilled. The test results are based on the level of difficulty of the questions with moderate criteria, the reliability of the test with Alpha Chronbatch is 0.75 with a good category, the discriminatory power of 76% with good category, and 60% of distractors function well. Analysis with Rasch modeling obtained 15 questions from 25 questions categorized as good to be used as a tool to measure students’ critical thinking skills. The assessment instrument developed has a good ability to measure students’ critical thinking skills, with 26.47% in the low ability category, 52.94% in the medium ability category, and 20.58% in the high ability category. Students' positive response to the use of critical thinking skills in the form of google form was 74.23%, with a good category. The product of the assessment instrument on the stoichiometric material developed is valid and meets the requirements for good quality questions, and can be used to measure students’ critical thinking skills.